Islamic approach in mitigating HIV AIDS - Ibrahim, Faisal (Community Health Society Malaysia, 2014)
In response to the devastating impact of HIV AIDS, Islamic approach to mitigate the epidemic is explored based on evidences acquired from Al-Qura’n and Sunnah (Prophet’s hadith, PBUH). These evidences cover the aspect of prevention, treatment, counseling, care and support, which are fundamentally required for alleviating the spread of HIV AIDS infection and its dreadful sequences on people infected and affected with HIV AIDS.